Philosophy-based Physical Education Management as a Foundation for Police Character Building in Indonesia - Nurhajati; Ahmad, Masduki; Suryadi, Suryadi (Journal Coaching Education Sports, 2025)
This study aims to explore the role of philosophy-based physical education management as a foundation in the formation of police character in Indonesia, using the literature review method. Physical education combined with philosophical values has great potential to not only develop physical abilities, but also shape moral character, ethics, and social awareness that are essential in the police profession. Through a literature review of related research, this article identifies five main aspects that can be developed through this approach: (1) improvement of discipline and moral responsibility, (2) strengthening of ethics and sportsmanship, (3) development of self-awareness and moral reflection, (4) formation of mental and emotional resilience, and (5) adaptation of local values in character building. The review shows that philosophy-based physical education can strengthen moral awareness and commitment to social responsibility in police candidates. By integrating philosophical principles such as Aristotelian ethics, self-reflection, and social values relevant to the Indonesian context, this approach enables learners to develop a fuller character that is aligned with the values of the police profession. This research suggests that police academies adapt philosophy-based physical education curricula, provide additional training for instructors, and adapt training programs to local values to produce police officers who are not only physically professional, but also have high integrity and social sensitivity.